Capital Intensity, Covenants, Distress, and Pressure: Drivers of Accounting Conservatism - Thio Anastasia Petronila; Natanael Delfiero; Juliana, Christina (Amkop Management Accounting Review (AMAR), 2025)
Accounting conservatism is a principle of prudence in financial reporting, where companies recognize potential losses and liabilities promptly while delaying the recognition of assets and earnings. This study aims to examine the influence of capital intensity, debt covenants, financial distress, and earning pressure on the application of accounting conservatism. The research focuses on non-financial companies listed in the LQ45 index during the 2021–2023 period. Using purposive sampling, 25 companies were selected, resulting in 75 observation units. Data were analyzed using descriptive statistics and multiple linear regression with IBM SPSS version 25. The findings reveal that capital intensity and debt covenants have no significant effect on accounting conservatism. However, financial distress has a negative effect, while earning pressure has a positive effect on the application of accounting conservatism. These results highlight the role of internal financial conditions in shaping conservative accounting practices, offering insights for managers, investors, and regulators regarding risk assessment and financial reporting strategies.